Pengaruh Stres Kerja, Komitmen Organisasional dan Kepuasan Kerja terhadap Turnover Intention Karyawan - Pranita Sari, Ni Made Risa; Wimba, I Gusti Ayu; Astawa, I Putu Putra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the effect of work stress, organizational commitment, and job satisfaction on turnover intention in KSP. The Main Gem of Tabanan. The population and sample in this study are all KSP employees. Permata Utama Tabanan which amounted to 34 people, The sampling method used is the census method, where the entire population is used as a research sample. The data collection method uses questionnaires that are distributed to respondents. The test techniques used are research instrument tests, classical assumption tests, multiple linear regression analysis, t tests and F tests. The results obtained in this study are: work stress has a positive and significant effect on partial turnover intention. Organizational commitment has a negative and significant effect on partial turnover intention. Job satisfaction has a negative and significant effect on partial turnover intention. Work stress, organizational commitment and job satisfaction have a significant effect on simultaneous turnover intention.